[Retracted Article] Mapping Research Trends of TikTok in Education: A Bibliometric Analysis - Siti Nurjanah; Shaufi Ramadhani; Zafrullah Zafrullah; D’aquinaldo Stefanus Fani Seran; Rooskartiko Bagas Rahoetomo; Sandry Rory (IJIE (Indonesian Journal of Informatics Education), 2024)
NOTICE OF ARTICLE RETRACTION Dear Readers and Stakeholders,We hereby announce that the article titled "Mapping Research Trends of TikTok in Education: A Bibliometric Analysis", published in IJIE (Indonesian Journal of Informatics Education), Volume 8, Issue 2 (December 2024), has been officially retracted from publication.Reason for Retraction:Following a thorough internal investigation, it was discovered that a violation of publication ethics was committed by the corresponding author. Specifically, the violation involved the addition of author names by editing the article metadata after the article had been accepted for publication. This act is deemed an exploitation of the publishing system by including authors whose contributions could not be clearly verified in the preparation of the article.This behaviour violates the principles of transparency, academic integrity, and the ethical publishing guidelines established by IJIE (Indonesian Journal of Informatics Education), as well as the standards set forth by the Committee on Publication Ethics (COPE).Further Actions:The article has been officially retracted and will be clearly marked as such on our publication platform.Information regarding this retraction will remain accessible to ensure transparency and accountability within the academic community.Further steps will be taken in accordance with our publication ethics policies.We reaffirm our commitment to upholding the highest standards of academic integrity and quality in scientific publishing. We sincerely apologise to our readers, contributing authors, and the wider scholarly community for any inconvenience caused by this matter.Thank you for your understanding and continued support. Yours sincerely,Editor-in-ChiefAbstract:This study aims to identify research trends related to the use of TikTok in the field of education using bibliometric analysis. Data was obtained from 46 publications obtained from the Scopus database in 2020–2023, which were filtered based on TikTok keywords in the context of education. Data analysis was carried out with the biblioshiny package of the RStudio application. The results showed that publications increased sharply in 2022. Geographically, China and the United States contributed the most. The main keywords included "social networking", "TikTok", and "students" representing the research trends on utilising TikTok for learning. The most cited articles indicate TikTok's potential as an innovative pedagogical tool to increase learners’ engagement and motivation and expand public access to education and health information. Further research was recommended to enrich multidisciplinary perspectives and maximise the benefits of TikTok for learning.